2011
DOI: 10.3238/arztebl.2011.0678
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis and Treatment of Eating Disorders

Abstract: This guideline contains evidence- and consensus-based recommendations for the diagnosis and treatment of eating disorders. If strictly implemented, it should result in improved care for the affected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 22 publications
2
56
0
9
Order By: Relevance
“…However, as some guidelines specifically recommend longer treatments for more severely ill patients (American Psychiatric Association, 2006;Herpertz et al, 2011), our findings may contribute to a critical evaluation of these recommendations. (4) Our sample is not representative for all patients with bulimia nervosa with regard to chronicity and symptom severity.…”
Section: Discussionmentioning
confidence: 76%
“…However, as some guidelines specifically recommend longer treatments for more severely ill patients (American Psychiatric Association, 2006;Herpertz et al, 2011), our findings may contribute to a critical evaluation of these recommendations. (4) Our sample is not representative for all patients with bulimia nervosa with regard to chronicity and symptom severity.…”
Section: Discussionmentioning
confidence: 76%
“…This suggests that as for AN the illness can enter stuck, treatment-resistant phase. Indeed a review in the German guidelines suggested there is only a moderate sized effect in terms of symptom change with standard treatments for bulimia nervosa (Herpertz, Vocks, Wietersheim, Cuntz, & Zeeck, 2011). Any model of bulimia nervosa needs to reflect this and to include maintaining factors.…”
Section: Models Of Bulimia Nervosamentioning
confidence: 98%
“…BN terimi ise yüksek kalorili yiyeceklerin daha fazla yenmesi için kontrol edilemeyen kusmaları tarif etmektedir. Kontrol edilemeyen aşırı yeme dönemini uzun açlık, kusma ve laksatif ve/veya diüretiklerin kötüye kullanımı takip eder 28 . Sürekli kusma sonucu ağızdan dışarı atılan asidik mide içeriği üst anterior dişlerin palatinal yüzey-lerinde düz ve parlak görüntü ile karakterize lingual erozyona sebep olur 29 .…”
Section: Beslenme Bozukluklarıunclassified